2007
DOI: 10.1143/jjap.46.6290
|View full text |Cite
|
Sign up to set email alerts
|

Development of Eu-Enhanced TiO2 Nanophotocatalyst for Effective Utilization of Spent Nuclear Fuel

Abstract: A UV-photoactive Eu-doped TiO2 nanoparticle activated with its wavelength-matched nanoscintillator is proposed for the effective utilization of spent nuclear fuel. The Eu-doped TiO2 nanoparticles were synthesized by the alkoxide-based sol–gel method at various doping concentrations and sintering temperatures. The X-ray diffraction (XRD) spectra revealed that the existence of the anatase phase of TiO2, which is favorable for photocatalytic application, was extended up to 800 °C by Eu doping. The average crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The RE ion doped nanoparticles were synthesized with the same method mentioned above [10], except for the addition of the corresponding RE dopant solution into the hydrolyser solution. The dopant solutions were prepared by dissolving RE chloride hydrates (EuCl 3 ·6H 2 O, SmCl 3 ·6H 2 O, 99.9%, Kojundo Chemical, Tokyo) in DI water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RE ion doped nanoparticles were synthesized with the same method mentioned above [10], except for the addition of the corresponding RE dopant solution into the hydrolyser solution. The dopant solutions were prepared by dissolving RE chloride hydrates (EuCl 3 ·6H 2 O, SmCl 3 ·6H 2 O, 99.9%, Kojundo Chemical, Tokyo) in DI water.…”
Section: Methodsmentioning
confidence: 99%
“…The average crystallite size for TiO 2 with various doping concentrations of Eu and Sm, sintered at 900 • C are given together with the nanoparticle size obtained from AFM[10] for the Sm doped one sintered at 950 • C. The mass fraction of anatase phase for RE doped TiO 2 films sintered at 900 • C shows that the domination of anatase phase is obtained at the same time with the abrupt reduction of crystallite size.…”
mentioning
confidence: 99%
“…The interest towards TiO 2 nanoparticles is also based on the fact that they can be applied as a photocatalytic material. Recent studies on Eu-doped TiO 2 nanoparticles [20][21][22][23][24][25] have reported that Eu doping particularly enhances the photocatalytic activity of TiO 2 in decomposing organic compounds. Additionally, our previous research showed that Eu ions effectively suppressed the growth of nanoparticles and stabilized the anatase phase, 26) which was advantageous for photocatalytic application.…”
Section: Introductionmentioning
confidence: 99%